In vitro evaluation of the anthelmintic activity of methanolic extracts of Guazuma ulmifolia against Cyathostominae nematodes - Castro Martinez, Paula Andrea (2023)
The study evaluated the anti-hatching effect of methanolic extracts from the bark and leaf of Guazuma ulmifolia using the in vitro Nematode Egg Hatching Inhibition test. Concentrations of 1000, 500 and 250 µg/ml of each extract, a negative control (Dimethyl sulfoxide) and two positive controls (Fenbendazole and Lugol) were evaluated against nematodes of the Cyathostominae subfamily as a biological model. The three concentrations of the two extracts, as well as the two positive controls showed statistically similar results, but different compared to the negative control. The mean inhibition of egg hatching using bark and leaf was 49.73 and 45.22%, respectively, at the 1000 µg/ml concentration, 61.93 and 59.20% at the 500 µg/ml concentration, and 75.60 and 75.82% at the concentration of 250 µg/ml. The methanolic extracts of the bark and leaf of Guazuma ulmifolia showed an anti-hatching effect against Cyathostominae nematodes at the concentrations tested.